Interference in Bilingual Ementary Students’ Conversations: A study of Bilingual Etudents at elementary Schools, Tondon - Rantepao – Toraja Utara - Rigel Sampelolo (Teaching English as a Foreign Language Overseas Journal, 2015)
Since the languages of the world come in contact, the society will experience something that called language contact and all of language phenomenon. Phenomenon that might be happening as the result of language contact is bilingualism. Bilingualism not only occurs in society but it also occurs in children language. When the bilingual children come in contact, there is bound to be a problem like interference which is a sociolinguistic phenomenon. This research focuses on language interference in bilingual elementary students by means of finding the types of interference and Factors Causing Occurrence of Interference. The findings proved that syntactic and semantic interference are types of interference that commonly occur in elementary students. Insufficient vocabulary receiver, The disappearance of words that are rarely used, The prestige of the source language and the language style, Entrainment habits in the mother tongue, and The user can not use the second language as good as first language are the factors causing the interference.